2023
DOI: 10.3390/w15234170
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Evaluation of Groundwater and Dam Reservoir Water: Application of the Water Quality Index to Study Sites in Greece

Kyriaki Kalaitzidou,
Maria Margarita Ntona,
Eythimia Zavridou
et al.

Abstract: To detect the degradation of clean water, it is necessary to characterize its quality through water quality indices using seasonal water sampling and analysis. In the present study, the initialization of the monitoring by surface and dam water sampling was conducted in multiple areas of Greece, including the Eastern Thermaikos Gulf, Mouriki, and Marathonas basins, during both the dry and wet periods of 2022. The dam reservoirs were also monitored by capturing their orthomosaic mapping. The classification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…One critical question regarding the application of MAR is the quality of dam water used for recharging. This was studied by Kalaitzidou et al [32], who concluded that dam water is suitable for MAR application.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One critical question regarding the application of MAR is the quality of dam water used for recharging. This was studied by Kalaitzidou et al [32], who concluded that dam water is suitable for MAR application.…”
Section: Methodsmentioning
confidence: 99%
“…The dam optimization code introduced by Karakatsanis et al [29] was used in this study to optimize the hydropower generation of the existing dams in the study areas. The geometrical characteristics were obtained from previous studies [32]. The code adopts a metaheuristic optimization model, leveraging the harmony search algorithm, representing a strategic approach to maximizing energy production while navigating a plethora of operational constraints.…”
Section: Dam Operation Modellingmentioning
confidence: 99%